2021
DOI: 10.1101/2021.03.12.21253015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diurnal variation in SARS-CoV-2 PCR test results: Test accuracy may vary by time of day

Abstract: False negative tests for SARS-CoV-2 are common and have important public health and medical implications. We tested the hypothesis that the proportion of positive SARS-CoV-2 real-time polymerase chain reaction (RT-PCR) tests varied by time of day, suggesting variation in viral shedding by time of day. Among 30,000 clinical tests performed among symptomatic and asymptomatic patients in the Vanderbilt Affiliated Healthcare Network from March-June 2020, we found evidence for diurnal variation in the proportion of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
1
8
2
Order By: Relevance
“…This may reflect differences between the cohorts studied, particularly with regard to immune status; we studied seronegative participants whereas responses to influenza vaccination will involve the stimulation of memory responses. Sample collection time in this study showed no significant association with anti-Spike levels, in contrast to previous reports (Kurupati et al, 2017;McNaughton et al, 2021). These data highlight the importance of It is worth noting that, despite the significant differences in anti-Spike levels detected in participants receiving Pfizer mRNA or AstraZeneca Adenoviral vaccines, both show comparable efficacies highlighting the robust nature of the host antibody response.…”
contrasting
confidence: 92%
“…This may reflect differences between the cohorts studied, particularly with regard to immune status; we studied seronegative participants whereas responses to influenza vaccination will involve the stimulation of memory responses. Sample collection time in this study showed no significant association with anti-Spike levels, in contrast to previous reports (Kurupati et al, 2017;McNaughton et al, 2021). These data highlight the importance of It is worth noting that, despite the significant differences in anti-Spike levels detected in participants receiving Pfizer mRNA or AstraZeneca Adenoviral vaccines, both show comparable efficacies highlighting the robust nature of the host antibody response.…”
contrasting
confidence: 92%
“…A study conducted in the United States in 2020 reported that positive tests showed a sinusoidal pattern with a peak point of 1:49 PM, 24 hours a day. 18 They also reported that the rate of positive tests at the peak point was 2.2 times higher than that at the lowest point of the curve. Therefore, the sinusoidal pattern in this study shows that the amount of virus in the mucosa varies with the cyclic pattern and the maximum amount at the beginning of each day.…”
Section: Discussionmentioning
confidence: 96%
“…A twofold variation was observed in the proportion of positive results across a 24 h period with a peak of positivity in the early afternoon (around 14.00). This suggests that the test results were most likely to be positive (less likely to be false negative) in the early afternoon compared with other times of day [ 12 ]. This observation is likely to be attributed to a combination of the circadian-regulated immune system and host pathways essential for SARS-CoV-2 replication, resulting in a fluctuation of viral shedding throughout the day.…”
Section: Viral Shedding May Be Dependent On the Time Of Daymentioning
confidence: 99%